Pharmacokinetics of Digoxin: Interpreting Bioavailability. Issue 5885 (20th October 1973) - Sanchez, N.; Sheiner, L. B.; Halkin, H.; Melmon, K. L.
Abstract : Three subjects were first given a digoxin tablet in the fasting state and subsequently received the same formulation in the fed state, to simulate a spurious oral bioavailability difference. As expected, when measured by peak serum digoxin concentration as well as by area under the serum digoxin concentration-time curve the bioavailability of digoxin appeared to be higher in the fasting state than in the fed state. However, when measured by cumulative five-day urinary excretion of digoxin bioavailability was identical in both conditions. This simple experiment illustrates the fact that the estimation of bioavailability is subject to considerable methodological error, of which the clinician must be aware when evaluating reports on drug bioavailability in general and of digoxin in particular.